Transformation Of Islamic Criminal Law: Dynamics Of Reform In The Contemporary Muslim World - Selvia Ramadhani; Zuyyina Mardhatillah; Ilma Dzumirrah; Dahyul Daipon (Indonesian Journal of Innovation Multidisipliner Research, 2026)
Islamic criminal law (fiqh jinayah) faces serious challenges in the modern era due to social change, technological advancement, and universal human rights demands. The tension between Islamic legal tradition and modernity raises fundamental questions regarding the conceptualization, urgency, and forms of legal reform, as well as the roles of society and government. This article aims to address these four issues through normative-juridical analysis and comparative legal studies of Muslim-majority states. The findings indicate four primary points. First, Islamic criminal law reform (tajdid) is not a total replacement but a contextual reconstruction grounded in maqashid al-syari’ah. Second, the urgency of this reform stems from historical-sociological, philosophical, and juridical dimensions to maintain legal relevance amidst changing times. Third, reform manifests through legal codification, contemporary ijtihad, reinterpretation of hudud provisions, and the adoption of relevant international legal concepts. Fourth, successful reform requires strategic synergy between the government as the legislative authority and societal elements-including scholars, academics, NGOs, and media—as epistemic and advocacy actors. Overall, this article asserts that the future transformation of Islamic criminal law depends on balancing sacred principles with contemporary human needs. Through an integrative approach, Islamic criminal law can evolve into a dynamic, just, and responsive legal system within global civilization without losing its fundamental religious identity.